Cardiac optical mapping – State-of-the-art and future challenges. (September 2020) - O'Shea, Christopher; Kabir, S. Nashitha; Holmes, Andrew P.; Lei, Ming; Fabritz, Larissa; Rajpoot, Kashif; Pavlovic, Davor
Highlights: Cardiac optical mapping is a fluorescent imaging method to study electrical behaviour and calcium handling in the heart. Optical mapping provides higher spatio-temporal resolution than electrode techniques, allowing unique insights into cardiac electrophysiology in health and disease from a variety of pre-clinical models. Both transmembrane voltage and intracellular calcium dynamics can be studied with the use of appropriate fluorescent dyes. Optical mapping has traditionally required the use of mechanical uncouplers, however computational and technical developments have lessened the requirement for these agents. Novel fluorescent dyes have been developed to optimise spectral properties, experimental timescales, biological compatibility and fluorescence output. The combination of these developments has made possible novel mapping experiments, including recent in vivo application of the technique. Abstract: Cardiac optical mapping utilises fluorescent dyes to directly image the electrical function of the heart at a high spatio-temporal resolution which far exceeds electrode techniques. It has therefore become an invaluable tool in cardiac electrophysiological research to map the propagation of heterogeneous electrical signals across the myocardium. In this review, we introduce the principles behind cardiac optical mapping and discuss some of the challenges and state of the art in the field. Key advancements discussed include newly developed fluorescent indicators, tools for the analysis of complex datasets, panoramic imaging systems and technical and computational approaches to realise optical mapping in freely beating hearts.